Internacjonalizmy - międzynarodowe słownictwo Unii Europejskiej w polszczyźnie = Internationalisms: Vocabulary of the European Union in Polish - Siewert-Kowalkowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Polish remains in constant contact with other languages whose influence can be seen in various areas, including the vocabulary of science, technology, politics, economics, law as well as of everyday life. Huge changes in contemporary Polish occurred particularly after the year 1989 as a result of the new social reality, and then, after Polish accession to the European Union in 2004.
Keywords: leksyka; internacjonalizacja; internacjonalizm; dokumenty unijne; vocabulary; internationalization; internationalism; EU documents